IMMUNO-PHARMACOTHERAPY OF CHILDREN WITH ALLERGIC DISEASES - V.A. Bulgakova; I.I. Balabolkin (Union of pediatricians of Russia, 2006)
The literature overview is dedicated to the application experience of immune response modifiers of various classes in treatment of allergic diseases among children. the authors of the article justify the prescription of immune response modifiers by frequent inter current acute respiratory diseases and complications of allergic pathology connected therewith on one hand and by the capability of immune response modifiers to change the activity of tymphocytes and inhibit the reproduction of Ige, thus, increasing the effectiveness of therapy in treatment of allergic diseases among children on the other hand.Key words: children, allergic diseases, respiratory infections, immunity, prevention, treatment, vaccines, immune response modifiers.